Financial Information Fraudulence and Financial Distress: Evidence from Singapore - et. al., Dalila Binti Abu Bakar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
We investigate if Singapore listed companies engaged in financial information fraud during financial distressed after two years of US subprime mortgage crisis. We also investigate the impact of financial information fraudulence in bankruptcy prediction and misclassification errors. This study used consumer product companies listed on the main board and the timeframe is from 2011 till 2015. The Altman Z score indicates that 55 out of 110 companies are financially distressed. Meanwhile, the M score shows that 49 out of 351 observations are engaged in financial information fraudulence. However, these results are relatively low because the samples are taken from the main board and fraudulence in their financial statements might be done in lower magnitude in order to avoid sanctions by the Security Exchange Commission. Logistic regression was used to measure the predicting accuracy. The result of the overall accuracy percentage slightly improved by 2.4 after eliminating fraudulent companies. The confusion matrix result i.e. before and after the removal of financial information fraudulent companies, the misclassification errors for type one has improved by 1.7 percent and 3 percent for type two. This result met objective three, as the upward bias of financial information fraudulence is one of the explanations for the decline in financial distress prediction. This research will be beneficial to governments, monitoring agencies, and all involved in the insolvency process.